2018
DOI: 10.1371/journal.pmed.1002581
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and sociodemographic variation of cardiovascular disease risk in India: A cross-sectional study of 797,540 adults

Abstract: BackgroundCardiovascular disease (CVD) is the leading cause of mortality in India. Yet, evidence on the CVD risk of India’s population is limited. To inform health system planning and effective targeting of interventions, this study aimed to determine how CVD risk—and the factors that determine risk—varies among states in India, by rural–urban location, and by individual-level sociodemographic characteristics.Methods and findingsWe used 2 large household surveys carried out between 2012 and 2014, which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
62
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 31 publications
15
62
2
Order By: Relevance
“…This proportion needs not only intensified lifestyle modification but drugs inclusion is a must in order to avert the impending CVDs. With respect to other similar studies, the prevalence of high risk of developing CVDs found in this study was in agreement with that of India (13.2%) [38] and the United States (15.5%) [39]. However, it was higher than those of rural India (10.2%) [15], Sri Lanka (2.2%) [40] and Cambodia (10.4%) [41] and lower than the Mongolian (33.3%) and Malaysian (20.8%) [41] studies.…”
Section: Discussionsupporting
confidence: 93%
“…This proportion needs not only intensified lifestyle modification but drugs inclusion is a must in order to avert the impending CVDs. With respect to other similar studies, the prevalence of high risk of developing CVDs found in this study was in agreement with that of India (13.2%) [38] and the United States (15.5%) [39]. However, it was higher than those of rural India (10.2%) [15], Sri Lanka (2.2%) [40] and Cambodia (10.4%) [41] and lower than the Mongolian (33.3%) and Malaysian (20.8%) [41] studies.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study established a higher risk of developing CVD among north Indians compared to inhabitants of other parts of India [13]. There are many risk factors which contribute to the present epidemic situation of CVDs in Indian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of a person’s total or absolute risk of a cardiovascular disease (CVD) event based on multiple risk factors is superior to assessment of single risk factors when identifying who is at greatest risk of a CVD event [ 1 ]. In this issue of PLOS Medicine , a study by Rifat Atun and colleagues outlines the use of CVD risk prediction equations for population health rather than for clinical purposes [ 2 ]. This has inherent appeal because risk stratification of a population could be used to drive policy and health service planning, inform funding decisions around subsidising treatments, and identify particular subgroups for more intensive intervention strategies.…”
Section: Cvd Risk Stratification For Population Healthmentioning
confidence: 99%